Theory for the World to Come Speculative Fiction and Apocalyptic Anthropology - Wolf-Meyer, Matthew J. (Forerunners: Ideas First, 2019)
Can social theories forge new paths into an uncertain future? The future has become increasingly difficult to imagine. We might be able to predict a few events, but imagining how looming disasters will coincide is simultaneously necessary and impossible. Drawing on speculative fiction and social theory, Theory for the World to Come is the beginning of a conversation about theories that move beyond nihilistic conceptions of the capitalism-caused Anthropocene and toward generative bodies of thought that provoke creative ways of thinking about the world ahead. Matthew J. Wolf-Meyer draws on such authors as Kim Stanley Robinson and Octavia Butler, and engages with afrofuturism, indigenous speculative fiction, and films from the 1970s and '80s to help think differently about the future and its possibilities. Forerunners: Ideas First Short books of thought-in-process scholarship, where intense analysis, questioning, and speculation take the lead